Ответы и объяснения

2014-02-22T17:54:28+04:00
3m(2n-k)=-3m(k-2n)
6mn-3mk=-3mk+6mn
6mn-6mn=-3mk+3mk
0=0
тождество доказано

  • Участник Знаний
2014-02-22T17:56:57+04:00
1) 3M * ( 2N - K ) = 6MN - 3MK 
2) - 3M * ( K - 2N ) = - 3MK + 6MN = 6MN - 3MK 
........................................................................
6MN - 3MK = 6MN - 3MK ( что требовалось доказать )
................................................................................
2 СПОСОБ:
- 3M * ( K - 2N) = 3M * ( - K + 2N ) = 3M * ( 2N - K )
3M * ( 2N - K ) = 3M * ( 2N - K ) ( что требовалось доказать )